Cardiopulmonary Profile in Streptozotocin-Induced Type 1 Diabetic Rats during Systemic Endotoxemia - Ching-Hsia Hung; Che-Ning Chang; Yu-Wen Chen; Yu-Chung Chen; Jann-Inn Tzeng; Jhi-Joung Wang (Journal of Diabetes Research)
This study was designed to determine the severity of cardiopulmonary dysfunction during systemic endotoxemia in type 1 diabetes. Thirty-two adult male Wistar rats were randomly assigned to a control group or to a group treated with streptozotocin (STZ) to create an animal model of type 1 diabetes. Survival time and cardiovascular parameters were continually monitored in urethane anaesthetized animals receiving intravenous infusion of endotoxin (lipopolysaccharide (LPS)) or saline. We also determined arterial blood gases, lung injury, and tumor necrosis factor-alpha (TNF-α) levels in serum and bronchoalveolar lavage fluid. Before LPS administration, the mean arterial pressure in STZ rats was significantly higher than that in normal rats. After LPS injection, the heart rate drop significantly in STZ rats than that in the control group. Also, the increased levels of TNF-α in serum and lavage fluid after LPS treatment were significantly higher in STZ rats than those in normal rats. Survival time in STZ rats was shorter than that in normal rats after LPS application. Albumin content, wet/dry weight ratio of lung, and lung injury were indistinguishable between STZ and normal rats. These results indicate that the cardiopulmonary change which occurs during LPS-induced endotoxemia is minor in STZ-induced diabetic rats.